Pendidikan Politik dalam Menangkal Pemahaman Radikalisme Agama Bagi Pemuda Muhammadiyah di Kecamatan Pariaman Utama, Kota Pariaman - Zulfadli Zulfadli; Sadri Chaniago; Heru Permana Putra (Warta Pengabdian Andalas, 2019)
This community service is caused by the tendency to strengthen the understanding of religious radicalism in society. Understanding radicalism obtained by the public along with developments in technology and information such as social media. In general, the understanding of radicalism has penetrated specific target groups such as young people. On the one hand, young people are among those who are vulnerable and potentially exposed to religious radicalism. On the other hand, young people are also potential groups in counter the understanding of religious radicalism. Community organizations such as Muhammadiyah have a strategic role in counteracting understanding of religious radicalism. Young people have a tactical and strategic role in counteracting the understanding of religious radicalism that tends to strengthen lately. Therefore, the seeding of thoughts, ideas, ideas of counter-radicalism and religious de-radicalism becomes relevant to carry out. The method used was a brainstorming technique, to find out the solution of a problem by gathering ideas spontaneously from group members. After that, it was then followed by a lecture method that ends up with a discussion. The results of this devotion showed an understanding of religious moderate for Muhammadiyah youth as a counter to understand the religious radicalism.